The effects of flunixin meglumine on viral shedding in calves - Neyland, Trey (My University, 2025)
Background – The effects of a Food and Drug Administration approved non-steroidal anti-inflammatory (NSAID) on viral shedding in cattle has not been investigated. Hypothesis/Objective - The hypothesis of this study was that flunixin meglumine would increase the magnitude and duration of viral shedding in calves inoculated with bovine herpesvirus-1 (BHV-1). Another objective was to investigate the consistency of BHV-1 shedding in inoculated calves. Animals - Twelve Holstein cross-bred steer calves, BHV-1 PCR-negative. Methods – In this randomized-control study, calves were randomized into treatment (FM) and control (CON) groups. All calves were inoculated intranasally with approximately 4-mLs of 1x10⁵ TCID₅₀ of BHV-1. Nasal swabs for BHV-1 PCR testing were collected every 24 hours following inoculation. Calves in the FM group were treated with 2.2mg/kg of flunixin meglumine intravenously after the first BHV-1 PCR positive sample. Magnitude and duration of viral shedding between groups was compared, and a p-value of <0.05 was considered significant. Results - The least square mean of the BHV-1 total log₁₀ AUC of the FM group was 6.11 (95% CI: 4.62-7.60) and CON group was 7.49 (95% CI: 6.00-8.98). The FM group's mean duration from initial to last positive BHV-1 PCR was 7.33 days (Range: 3-12, SD: 4.41), and the CON group's mean was 9.5 days (Range: 1-17, SD: 5.80). There was a treatment-by-time interaction, and there was no difference in BHV-1 shedding by treatment group when comparing mean log₁₀ TDIC₅₀. Conclusions and Clinical Importance – Intranasal inoculation with BHV-1 had a wide range of shedding magnitude and duration. Flunixin meglumine administration in BHV-1 challenged calves did not result in an increase in magnitude or duration of viral shedding.
Keywords: Non-steroidal anti-inflammatory; Flunixin meglumine; Viral shedding